Sustainable use of polypropylene fibers and palm oil fuel ash in the production of geopolymer concrete. Issue 1 (June 2021) - Adapala, Bala Gopal; Kumar Jagarapu, Durga Chaitanya; Jeelani, Syed Hamim; Sarath Chandra Kumar, B.; Eluru, Arunakanthi
Abstract: Geopolymer concrete is an innovative advance in the world, in this concrete cement is fully substituted with pozzolanic materials like fly ash and GGBS. In this present study fly ash is replaced with POFA (Palm oil fuel ash) up to 25% (0%, 5%, 10%, 15%, 20%, 25%), 10% of stone dust is replaced with sand. In addition to the above materials, 0.2% of polypropylene fibers were added to the volume of concrete. 2.5 ratio of sodium silicate and sodium hydroxide solutions are added as Alkali activators for 10M molarity. Initially, the specimens are oven cured 80° C for about 24hrs and after that leave for ambient curing. All the specimens stood tested after 7 and 28 days of ambient curing. The prepared POFA based geopolymer was tested for all types of mechanical properties, like compressive strength, split tensile strength, bending strength and load deflection curve. All these properties are compared with the nominal concrete.